2013
DOI: 10.1186/1471-2334-13-66
|View full text |Cite
|
Sign up to set email alerts
|

Safety and efficacy of high-dose daptomycin as salvage therapy for severe gram-positive bacterial sepsis in hospitalized adult patients

Abstract: BackgroundIncreasing the dosage of daptomycin may be advantageous in severe infection by enhancing bactericidal activity and pharmacodynamics. However, clinical data on using daptomycin at doses above 6 mg/kg in Asian population are limited.MethodsA retrospective observational cohort study of all hospitalized adult patients treated with daptomycin (> 6 mg/kg) for at least 72 hours was performed in Taiwan.ResultsA total of 67 patients (40 males) with a median age of 57 years received a median dose of 7.61 mg/kg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
33
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(35 citation statements)
references
References 31 publications
2
33
0
Order By: Relevance
“…However, Sakoulas et al found that a dosage of 40 mg/kg in rats is comparable to a dosage of 6 mg/kg in humans (19). Hence, the dosage of 60 mg/kg in rats used in the present study appears comparable to the increasingly higher doses of daptomycin applied in humans currently (20).…”
Section: Discussionmentioning
confidence: 67%
“…However, Sakoulas et al found that a dosage of 40 mg/kg in rats is comparable to a dosage of 6 mg/kg in humans (19). Hence, the dosage of 60 mg/kg in rats used in the present study appears comparable to the increasingly higher doses of daptomycin applied in humans currently (20).…”
Section: Discussionmentioning
confidence: 67%
“…The existence of a relationship between the daily dose and the occurrence of DIMT has been assessed in some studies that compared HD with SD daptomycin [5,9,13,74,75]. In the study by Lai et al, the incidence of CPK elevation was significantly higher in patients treated with daptomycin >8 mg/kg compared with ≤8 mg/kg (16.7% vs. 0%; P = 0.02) [9].…”
Section: Safety Of High-dose Daptomycin Therapymentioning
confidence: 97%
“…In the study by Lai et al, 67 patients, the majority of whom were treated in intensive care units for miscellaneous infections with daptomycin at a median daily dose of 7.61 mg/kg (range 6.03-11.5 mg/kg) for a median duration of 14 days, had an outcome unrelated to the daily dosage of daptomycin (i.e. ≥8 mg/kg or <8 mg/kg) [9]. Similar results were found in a single-centre retrospective study in which time to microbiological cure was assessed in 46 patients, including 28 (61%) neutropenic patients with bacteraemia due to Enterococcus spp.…”
Section: Clinical Data Justifying the Use Of High Dosesmentioning
confidence: 97%
See 1 more Smart Citation
“…The lack of an impressive change in the mean probabilities of clinical success and decreased susceptibility was expected, as the daptomycin AUC and, thus, dose would need to more than double (e.g., the dose would need to increase from 6 to 12 mg/kg/day) to provide exposures adequate to cover a 1-dilution increase in the MIC. Increasing numbers of reports and amounts of data from clinical studies provide support for the use of higher doses of daptomycin (8 to 12 mg/kg/day) to improve outcomes among patients with serious and life-threatening infections (21)(22)(23)(24)(25)(26). The results of simulations conducted to evaluate the mean probabilities of favorable outcomes with daptomycin at 8 and 10 mg/kg/day should be interpreted with some caution since the exposures and model-predicted probabilities estimated were at or beyond those for the exposure range studied; thus, some degree of extrapolation was required.…”
Section: Discussionmentioning
confidence: 99%